The Portuguese free radio movement in the Southern European context1, 2. (1st October 2014) - Santos, Susana
The main objective of this article is to provide an understanding of the Portuguese free radio movement while at the same time presenting it as a part of the Southern European movement. Theoretically, we use the concept of media system provided by Hallin and Mancini – in particular, the polarized pluralist model used to describe the Mediterranean countries. The Portuguese movement shared with its Greek counterpart some of the characteristics associated with the sharing and enjoyment of music. Comparison with the French free radio movement allows us to frame the reaction of the Portuguese party political system to the illegal broadcasting phenomenon. The methodological strategy is based on the triangulation of information sources. A total of fifteen in-depth interviews were conducted with free radio activists, parliamentarians and journalists, and press reports and parliamentary debates between 1983 and 1988 were subjected to content analysis. With the study of the recent past we want to contribute towards the public debate about mass media in subjects like regulation and the state, pluralism and public service, media economic groups, freedom of information and expression, and citizenship rights.